2015
DOI: 10.1186/s12864-015-1991-5
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations in the genome of the Qatari population

Abstract: BackgroundThe populations of the Arabian Peninsula remain the least represented in public genetic databases, both in terms of single nucleotide variants and of larger genomic mutations. We present the first high-resolution copy number variation (CNV) map for a Gulf Arab population, using a hybrid approach that integrates array genotyping intensity data and next-generation sequencing reads to call CNVs in the Qatari population.MethodsCNVs were detected in 97 unrelated Qatari individuals by running two calling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The efficacy of this array was rather poor, with 40.54% of CNVs that were tagged at r 2 > 0.5 and 21.17% in strong LD. Similar findings were observed in the CNV study in the Qatari population when using the Illumina OMNI2.5M array 16 . This taggability gap could be attributed to the local SNP density paucity, thus influencing the LD level.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The efficacy of this array was rather poor, with 40.54% of CNVs that were tagged at r 2 > 0.5 and 21.17% in strong LD. Similar findings were observed in the CNV study in the Qatari population when using the Illumina OMNI2.5M array 16 . This taggability gap could be attributed to the local SNP density paucity, thus influencing the LD level.…”
Section: Discussionsupporting
confidence: 86%
“…A comparative LD analysis using two different SNP sets genotyped by different SNP arrays revealed that ~80% of CNVs are in high LD ( r 2 > 0.8) when HapMap phase 2 SNP set was used compared to ~50% of CNVs that were in high LD with commercial SNP array sets 18 . An improvement of this taggability has been obtained with whole-genome sequencing SNPs as >70% of the deletions have been tagged by at least one SNP at r 2 > 0.5 and over 50% at r 2 > 0.8 in the Qatari dataset in agreement with LD data generated using 1000 Genome dataset 15 , 16 . Consequently, this fact suggests that CNV genotyping could be challenging using this or other commercial arrays in North African populations.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The superior performance of cn.MOPS on WGS and WES data has already been demonstrated (Guo et al., ; Klambauer et al., ). Specifically, cn.MOPS has been used to detect CNVs in the Taiwanese Han and Qatari populations (Fakhro et al., ; Lin, Tseng, Jeng, & Sun, ), in individuals with intellectual disability (Schuurs‐Hoeijmakers et al., ), and in patients with early‐onset neuropsychiatric disorders (Brand et al., ). cn.MOPS builds a local model that captures the read characteristics of each ROI.…”
Section: Introductionmentioning
confidence: 99%